SENSITIZING EFFECT OF CURCUMIN ON CISPLATIN-INDUCED APOPTOSIS INVOLVES SUPEROXIDEANION INDUCTION AND BCL-2 DEGRADATION - Chanvorachote, P.; Pongrakhananon, V.; Luanpitpong, S.; Nimmannit, U. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The possibility of using curcumin as a chemotherapeutic sensitizing agent has been intensively demonstrated in some cancers. However, the effect of curcumin on non-small cell lung cancer (NSCLC), one of the most resistant cancers, is largely unknown. The aim of this study was to investigate the sensitizing effect of curcumin on cisplatin-induced apoptosis in NSCLC cells. Curcumin was shown to induce intracellular superoxide anion generation, down-regulate anti-apoptotic Bcl-2 protein, and subsequently sensitize NSCLC H460 cells to cisplatin-induced apoptosis. Amplification and overexpression of bcl-2 protein has been implicated in chemotherapeutic resistance in many cancers and overexpression of this protein strongly rendered H-460 cells resistant to cisplatin-induced apoptosis. The present study showed that co-treatment of the cells with curcumin and cisplatin resulted in increased apoptosis and reversal of Bcl-2-mediated cisplatin resistance. The mechanism by which curcumin down-regulates Bcl-2 and sensitizes cells to cisplatin-induced apoptosis involves proteasomal degradation of Bcl-2, since a specific proteasome inhibitor lactacystin reversed effect of curcumin on bcl-2 level. These findings indicate a novel pathway for curcumin regulation of Bcl-2, which benefits the development of a cisplatin sensitizing agent.